Development of Preparation of Exercise Programs to Improve Physical Fitness Through Applications to Banyuasin III Men's Volleyball Club Athletes - Heri Nugroho; Iyakrus Iyakrus; Wahyu Indra Bayu; Meirizal Usra; Hartati Hartati; Syafaruddin Syafaruddin (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
This study aims to determine the development of the preparation of the right exercise program to improve the physical fitness of athletes through the application at the Banyuasin III Men's Volleyball Club. The research and development method used is the Borg and Gall model, with data collection techniques in the form of observation, tests, and questionnaires. The data obtained from the results of this study will be analyzed to determine the quality of developing an exercise program in improving physical fitness using an analysis of validity, practicality, and effectiveness. The results of the study concluded that the resulting product was an exercise program to improve the physical fitness of athletes consisting of 6 posts at each meeting and compiled based on input and advice from coaching experts, exercise program experts, and fitness experts. The product that has been created has been tested on a small scale with 10 volleyball athletes, on a large scale with 25 volleyball athletes, and has met the validity, practicality, and effectiveness tests. The implications of developing this training program are very good so that it can be used by athletes, especially volleyball and generally other sports athletes as needed.